Paleoceanographic inferences from benthic foraminifera across the early Aptian Ocean Anoxic Event 1a in the western Tethys - Victor Giraldo-Gómez; Maria Rose Petrizzo; Elisabetta Erba; Cinzia Bottini (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
The paleoenvironmental impact of the early Aptian Ocean Anoxic Event 1a (OAE 1a, ca. 121 Ma) has been investigated in detail in the Cismon Core (Lombardy Basin, western Tethys) by using different geochemical and micropaleontological proxies. We provide the first high-resolution data of benthic foraminiferal assemblages through the upper Barremian - lower upper Aptian stratigraphic interval. Benthic foraminifera data are integrated with calcareous nannofossil and planktonic foraminifera records to create a comprehensive characterization of bottom and surface waters across OAE 1a. Benthic foraminiferal communities are indicative of a marked change in bottom-waters around the “nannoconid decline” (latest Barremian) due to increased flux of organic matter to the seafloor and intermittent dysoxic conditions probably promoted by pulses of higher productivity during the initial Greater Ontong Java Event (GOJE). Benthic foraminifera experienced a marked crisis in abundance (“benthic foraminiferal crisis” BFC) ca. 35 kyr before the OAE 1a, in correspondence with the “nannoconid crisis” and the onset of the most intense GOJE phase. The literature survey shows that the BFC is commonly recorded before the OAE 1a onset in several stratigraphic sections worldwide, and therefore, it is here proposed as a global event. At Cismon, deep-water anoxia was reached at the OAE 1a onset and lasted for ca. 300 kyr, promoted by higher productivity and eventually enhanced water stratification during the super-greenhouse climate. The continuation of OAE 1a was marked by a benthic foraminiferal repopulation event, probably resulting from the influx of relatively cooler and oxygenated waters. In turn, the OAE 1a was marked by intermittent anoxic to dysoxic conditions, likely in response to primary productivity sustained by N-fixing bacteria. The distribution and abundance of benthic foraminifera documented in other sections across the Selli Level equivalent show different features that point to local factors such as paleodepth and increased ...